A single session of mindfulness meditation may acutely enhance cognitive performance regardless of meditation experience - Rita Sleimen-Malkoun; Louise Devillers-Réolon; Jean-Jacques Temprado (PLoS ONE, 2023)
The present study investigated acute cognitive effects of mindfulness meditation (MM) compared to an active control intervention in meditators (n = 22) and novices (n = 20) using a within-subject design. We analyzed reaction times in a digitized Stroop task at baseline, after a 10-minute MM session with a fundamental breathing exercise, and after a 10-minute attentive listening intervention. Interventions order was randomized and a 10 min delay was respected before testing. Relative to baseline, meditators and novices showed faster reaction times after both interventions, but more so after MM for the congruent and incongruent Stroop task conditions that are associated with attention, inhibition and cognitive flexibility. Although the two interventions showed cognitive effects independent of previous meditation experience, MM appeared to induce larger benefits. Our findings are encouraging and support MM’s potential as a means to enhance cognitive performance on the short-term without the need of any previous practice.